Major diseases of kacholam (kaempferia galanga L.) and their management - Priya K (Department of Plant Pathology, College of Horticulture, 2005)
A study on “Major diseases of Kacholam [Kaempferia galanga L.] and their management” was conducted at College of Horticulture, Vellanikkara during 2003-2004. The study revealed that Ralstonia solanacearum (Smith) Yabuuchi et al., Colletotrichum gloeosporioides (Penz.) Sacc, Colletotrichum capsici (Syd.) Butler and Bisby were major pathogens in Kacholam. Ralstonia solanacearum was the major pathogen causing wilt in Kacholam. Among the 12 genotypes of kacholam tested two genotypes were immune to wilt and nine were highly resistant to leaf spot disease.